Investigation of the mechanical properties of heat-protective highly porous composite materials using the effective medium model - N.A. Kucheva, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The paper proposes a method for studying the mechanical properties of heat-shielding highly porous materials using an effective medium model. The mechanical characteristics of the composite material are calculated depending on the orientation angle and the volumetric content of the fibers. Stress-strain diagrams in tension and compression are plotted parallel and perpendicular to the plane.